(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
A geophysical ground magnetic survey method was used to investigate the presence and depths of magnetic minerals at Ijeda, Oriade Local Government area of Osun-State Nigeria. A G856AX Proton precession magnetometer was used to acquire 122 magnetic data points partitioned into 11 profiles. The station intervals and spacing were 10 m and 5 m respectively between each profile. Regional gradient and the effect of a geomagnetic reference field were removed from the observed survey data, the residual anomalies obtained were plotted against distance using Microsoft excel. Analytic Signal Method (ASM) and Peter’s Half Slope Method (PHSM) were utilized in estimating average Magnetic Source Depths. The Obtained magnetic data were plotted as 1-grid vector map, 2-D contour map and 3-D surface distribution map using surfer application to produce the qualitative analysis. The maximum and maximum magnetic intensity values obtained were 25.0 nT and -41.8 nT respectively, which suggested the area of magnetic mineral occurrences. The depths to the magnetic sources were calculated for 11 profiles and the average depth values ranged from 3.93 m ± 1.22 to 7.34 m ± 1.55 using both the ASM and the PHSM. The results showed that the study area holds a very good potential for magnetic mineral exploration.